Potential of the coffee endophytic Bacillus cereus sensu lato strain CCBLR15 to control the plant-parasitic nematode Radopholus duriophilus. Issue 8 (3rd August 2022) - Duong, Benoit; Marraccini, Pierre; Etienne, Hervé; Villain, Luc; Hoang, Giang Thi; Khong, Giang Ngan; Lebrun, Michel; Duponnois, Robin
ABSTRACT: Bacillus cereus sensu lato strain CCBLR15 is highly efficient in inducing in vitro the mortality of coffee-parasitic nematodes, including Pratylenchus coffeae and Radopholus duriophilus . In the present study, this strain was further characterised to investigate (1) its taxonomic position, (2) the secreted/non-secreted nature of its nematicidal compounds, and (3) its in planta biocontrol capacity towards R. duriophilus . Firstly, analysis of 16S rRNA gene sequences and motility test indicated that CCBLR15 was closely related to B. cereus sensu stricto. Secondly, nematodes separate expositions in vitro to CCBLR15 culture filtrate and cell lysate revealed that nematicidal activity was attributed to compounds released after bacterial cell lysis. Thirdly, CCBLR15 nematode biocontrol capacity was studied using three Coffea arabica cultivars, either seed- or cutting-propagated. Plants were therefore characterised by different developmental stages, referred to as 'early' and 'advanced', with respectively 2-3 and 6-8 leaf pairs. Additionally, plants were grown in unsterilised soil, with a one-month delay between inoculations of bacteria and nematodes to assess the persistence of the nematicidal effects. The presence of R. duriophilus in roots decreased plant growth only in one cultivar whose plants were inoculated at the 'early' stage. Nonetheless, CCBLR15 pre-inoculation significantly reduced the number of nematodes in roots of all cultivars and inhibited the negative effects of nematodes in 'early'-inoculated plants. These results demonstrate the capacity of CCBLR15 to control R. duriophilus and constitute an important step before studying the persistence of its biocontrol effects on a longer period or after plants establishment in the field.